Electrochemical, spectroelectrochemical, and dielectric properties of metallophthalocyanines bearing redox active cobalt and manganese metal centres - KOCA, ATIF (ELSEVIER SCIENCE SA, 2017)
We report herein the synthesis of symmetrical metallophthalocyanines having cobalt, zinc, and manganese as the metal ions, and having tetrakis(4-phenyl-1,3-thiazole-2-thiolate) groups substituted at the peripheral positions of the phthalocyanine. Electrochemical responses of the complexes were determined with voltammetric and in situ spectroelectrochemical measurements. Cobalt and mu-oxo manganese phthalocyanines (CoPc and mu-oxo MnPc) illustrated metal-based electron transfer reactions in addition to the Pc based reactions.-oxo-manganese phthalocyanine exhibited completely different redox properties than those of the monomeric manganese phthalocyanine. Thiazole substituents of the complexes caused oxidative electropolymerisation of the complexes on the working electrode. Electropolymerised-oxo manganese phthalocyanine catalyzed oxygen evolution reaction (OER) in basic aqueous solution. The ac behaviour of the tetrasubstituted metallophthalocyanines was studied by impedance spectroscopy technique over a temperature range of 300-450 K and frequency of 100 Hz-13 MHz. The results show that the new compounds exhibit abnormally high dielectric constants even at room temperature. It was concluded that Maxwell-Wagner polarisation is an appropriate model to explain the behaviour of the dielectric function at low frequencies. Frequency dependent measurements revealed that the compounds exhibits non-Debye type relaxation behaviour. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Phthalocyanine; Thiazole; Aggregation; Spectroelectrochemistry; Dielectricity; MICROWAVE-ASSISTED SYNTHESIS; PHTHALOCYANINES SYNTHESIS; SUBSTITUTED COBALT; IRON; NICKEL; BEHAVIOR; FILMS